2020
DOI: 10.1111/bjhp.12421
|View full text |Cite
|
Sign up to set email alerts
|

Depression in people with skin conditions: The effects of disgust and self‐compassion

Abstract: Objectives. Skin conditions can be accompanied by significant levels of depression; there is therefore a need to identify the associated psychological factors to assist with the development of appropriate interventions. This study sought to examine the effects of disgust propensity, disgust sensitivity, self-focused/ruminative disgust, and self-compassion on depression in people with skin conditions. Design. A cross-sectional survey with follow-up survey. Methods. Dermatology outpatients (N = 147) completed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…As self-compassion is expected to promote behaviors that enhance or maintain wellbeing ( 15 ), people with skin conditions who are high in self-compassion are expected to take appropriate steps to manage skin-related distress, thus lessening its impact. Consistent with this notion, there is evidence to suggest that self-compassion helps protect against depression in dermatological outpatients ( 9 ).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…As self-compassion is expected to promote behaviors that enhance or maintain wellbeing ( 15 ), people with skin conditions who are high in self-compassion are expected to take appropriate steps to manage skin-related distress, thus lessening its impact. Consistent with this notion, there is evidence to suggest that self-compassion helps protect against depression in dermatological outpatients ( 9 ).…”
Section: Introductionmentioning
confidence: 82%
“…The study was advertised via the University of Sheffield's volunteer list and social media (Facebook and Twitter). Consenting participants from a previous study ( 9 ) were also invited to take part. A purposive sample was formed by asking volunteers to complete an online screening survey, which consisted of the Self-Compassion Scale–Short Form (SCS–SF; 22 ), the PHQ-2 (a depression screener; 23 ) and questions about the skin condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broken skin (skin that has fissures, cracks, bleeds etc. ), such as in ichthyosis, may elicit disgust (Clarke, Thompson, & Norman, 2020 ), a concept that is understudied in research in the dermatologic field (Mento, Rizzo, Muscatello, Zoccali, & Bruno, 2020 ). Within clinical care, healthcare professionals may not feel confident in exploring this topic with parents or individuals with skin disorders such as ichthyosis.…”
Section: Discussionmentioning
confidence: 99%
“…The PSP for acne contains little psychological focus despite several acne studies, including a recent UK study with over 2000 participants, 6 indicating the importance of psychological issues for patients with acne. The results of the survey, which ran from 2012 to 2019, showed that people with acne vulgaris often experience significant psychosocial burden, including suicidal ideation and self‐harm 7 . The lack of psychological focus in the acne PSP may be related to the idiosyncrasies of the PSP process, but it is important to point out that, for patients and many healthcare professionals, psychological and psychiatric factors are key research questions that need addressing.…”
Section: Skin Condition ‘Top 10’ Psp Research Areas Positionmentioning
confidence: 99%